2018
DOI: 10.1101/354761
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recent mixing of Vibrio parahaemolyticus populations

Abstract: 20Background Humans have profoundly affected the ocean environment but little is known 21 about anthropogenic effects on the distribution of microbes. Vibrio parahaemolyticus is found 22 in warm coastal waters and causes gastroenteritis in humans and economically significant 23 disease in shrimps. 24Results Based on data from 1,103 genomes, we show that V. parahaemolyticus is divided 25 into four diverse populations, VppUS1, VppUS2, VppX and VppAsia. The first two are 26 largely restricted to the US and Northe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 31 publications
0
24
1
Order By: Relevance
“…For each interaction group, we investigated how genetic variation was structured within the V. parahaemolyticus population using a larger “non-redundant” set of 469 strains, which includes isolates from all four of the populations identified in (8), but excludes closely related isolates, differing at less than 2,000 SNPs. We performed hierarchical clustering of the strains based on the interaction group variants (Figure 3, 4, 5, S2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For each interaction group, we investigated how genetic variation was structured within the V. parahaemolyticus population using a larger “non-redundant” set of 469 strains, which includes isolates from all four of the populations identified in (8), but excludes closely related isolates, differing at less than 2,000 SNPs. We performed hierarchical clustering of the strains based on the interaction group variants (Figure 3, 4, 5, S2).…”
Section: Resultsmentioning
confidence: 99%
“…Totally 1,103 global V. parahaemolyticus genomes were used in this work (Table S1), which also were analyzed in our other studies (8, 10). To reduce clonal signals, we firstly made a “non-redundant” dataset of 469 strains, in which no sequence differed by less than 2,000 SNPs in the core genome.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As phage VP882 has the capacity to activate lysis in response to host DPO production, we wondered whether mutations in the phage-encoded QS pathway similarly arise. As one example, we identified a curious 8.5 kb contig (GenBank: NNHH01000051.1) in a recent dataset from mixed V. parahaemolyticus populations (Yang et al, 2019) (Figure S6B). The contig spans the region where vqmAPhage and qtip are located in phage VP882, between two conserved genes, repA and telN (Silpe and Bassler, 2019a).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Rehnstam‐Holm, Atnur, and Godhe (2014) also reported that the occurrence of V. parahaemolyticus in offshore areas of the southwest coast of India in the Arabian Sea was positively correlated with the abundance of copepods. Evidence suggests that zooplankton and copepods facilitate the oceanic dispersal of V. parahaemolyticus populations (Martinez‐Urtaza et al., 2012; Rehnstam‐Holm et al., 2014), which facilitates the spread of V. parahaemolyticus infections (Raszl, Froelich, Vieira, Blackwood, & Noble, 2016; Yang et al., 2019). A study by Martinez‐Urtaza et al.…”
Section: Effects Of Pressures Of Climate Change On the Risk Of V Parmentioning
confidence: 99%